The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3310/hta20780-c201803
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: A systematic review and economic evaluation of bisphosphonates for the prevention of fragility fractures

Abstract: During the course of providing additional analyses for the National Institute for Health and Care Excellence Technology Appraisal Committee, two errors were identified in the data entered in the network meta-analysis that informed the cost-effectiveness analysis described in the original report. This corrigendum notice describes the errors identified and the impact of correcting these errors on the main analyses presented in the original report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…149 Table 37 of the analysis underpinning TA464 150 has something similar, although note that this is based on an uncorrected network metaanalysis, and the corrigendum does not include an updated version of the same information. 147 Whether adjusted for competing risk or not, the updated model estimates that alendronate prevents slightly more fractures than the previous models in all categories except wrist fracture, and this is because the longer duration of treatment (and consequent extension of offset period) gives more time for the intervention to provide benefit. The reduced efficacy for wrist fracture compared with the 2020 HTA 149 is probably a result of different inputs, for example the network meta-analysis developed for the 2020 HTA 149 included a wider range of comparators and estimated a greater mean effect for bisphosphonates in preventing wrist fractures.…”
Section: Accounting For Competing Riskmentioning
confidence: 94%
See 3 more Smart Citations
“…149 Table 37 of the analysis underpinning TA464 150 has something similar, although note that this is based on an uncorrected network metaanalysis, and the corrigendum does not include an updated version of the same information. 147 Whether adjusted for competing risk or not, the updated model estimates that alendronate prevents slightly more fractures than the previous models in all categories except wrist fracture, and this is because the longer duration of treatment (and consequent extension of offset period) gives more time for the intervention to provide benefit. The reduced efficacy for wrist fracture compared with the 2020 HTA 149 is probably a result of different inputs, for example the network meta-analysis developed for the 2020 HTA 149 included a wider range of comparators and estimated a greater mean effect for bisphosphonates in preventing wrist fractures.…”
Section: Accounting For Competing Riskmentioning
confidence: 94%
“…The analysis concluded that oral bisphosphonates are likely to represent an effective use of NHS resources for anyone whose 10-year risk of MOF exceeds 1.5%. 147 The same authors updated their model as part of a further health technology assessment (HTA) for a subsequent NICE appraisal, and this focused on antiosteoporosis medicines other than bisphosphonates, but included bisphosphonates as comparators, although NICE subsequently chose to suspend the appraisal. 148 The updated model found that a somewhat higher level of risk, than in TA464, 12 would be necessary for oral bisphosphonates to provide reasonable value for money, although the precise threshold is not quantified.…”
Section: Selection Of the Case Studymentioning
confidence: 99%
See 2 more Smart Citations